2019
DOI: 10.1590/1413-7054201943000219
|View full text |Cite
|
Sign up to set email alerts
|

Quality and antioxidant potential of ‘BRS clara’ and ‘Arizul’ grapes influenced by rootstocks in a tropical region

Abstract: Seedless table grapes cultivars have been studied in the Sub-middle region of São Francisco Valley at northeast Brazil. For that region, it is important to identify cultivars with productive potential, better quality and efficiency, minimizing the expenses in terms of inputs and workforce, when compared to traditional cultivars. Specifically, the objective of this study was to determine the influence of different rootstocks on the quality and on the antioxidant potential of BRS Clara and Arizul table grapes cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…IAC 313 and IAC 572 led to an increase in the berry size of BRS Clara, as a result of less competition for photoassimilates in bunches with low fruit set and a smaller number of berries. Brito et al (2019) found values for bunch weight similar to those observed in this study, although with marked differences between two production cycles in the same cultivar and experimental area. In addition to the rootstock, bunch management practices considerably affect berry weight and size in the BRS Clara; bunch thinning and two applications of 30 mg.L -1 gibberellic acid are recommended to increase bunch weight and berry diameter (Formolo et al 2009).…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…IAC 313 and IAC 572 led to an increase in the berry size of BRS Clara, as a result of less competition for photoassimilates in bunches with low fruit set and a smaller number of berries. Brito et al (2019) found values for bunch weight similar to those observed in this study, although with marked differences between two production cycles in the same cultivar and experimental area. In addition to the rootstock, bunch management practices considerably affect berry weight and size in the BRS Clara; bunch thinning and two applications of 30 mg.L -1 gibberellic acid are recommended to increase bunch weight and berry diameter (Formolo et al 2009).…”
Section: Resultssupporting
confidence: 87%
“…Tecchio et al (2009) observed that A Dona grown on the rootstock IAC 766 in the state of São Paulo had greater bunch weight and berry size than those found in this study, which may be explained by the treatments with gibberellic acid. In contrast, results obtained in the same experimental area by Brito et al (2019) indicate similar values for berry weight, but lower values for bunch weight and titratable acidity than those observed in this study.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…The total phenol concentration of the three rootstocks employed was greater than that reported by Ahmed et al (2019) [1] for 'BRS Isis' grapes grafted onto 'IAC 766' in a tropical environment (26.1 mg 100 g −1 ). Lower levels of total phenols were also reported in 'Redglobe' [47] and 'BRS Clara' [48] grapes grafted onto 'Paulsen 1103', namely 97.413 mg 100 g −1 and 81.39 mg 100 g −1 , respectively. These findings highlight the great diversity in the rootstock's effect on the biosynthesis and composition of these chemicals [49], as well as the direct influence of climatic factors such as temperature, light, and precipitation [1].…”
Section: Chemical Properties Of the Grape Mustmentioning
confidence: 82%
“…Brito et al (2019) [ 35 ], after determining the physicochemical characteristics of BRS Clara grapes, observed marked differences in relation to the two productive cycles analyzed, which resulted among all rootstocks in mean SS/TA values of 54.6 and 23.6. This index helps in deciding the ideal moment for harvest; because SS and TA have an inverse evolution relationship, they tend to be similar in relation to the evolution of SS, i.e., there is a progressive increase in SS/TA values until the period near the harvest [ 39 ].…”
Section: Resultsmentioning
confidence: 99%